2019
DOI: 10.17712/nsj.2019.3.20180041
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of stroke among patients attending primary healthcare services in Abha, Southwestern Saudi Arabia

Abstract: Improving stroke-related knowledge may advance stroke prevention and reduce pretreatment delay and disabilities. Methods: We conducted a cross-sectional study among a representative sample of primary healthcare adult patients between January-May 2016 and used a validated Arabic questionnaire to evaluate the participants' awareness about stroke. Results: The study involved 1472 adults. Only 63.6% and 43.7% of participants correctly recognized thrombosis and hemorrhage as types of stroke. Commonly identified ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
(34 reference statements)
3
22
0
Order By: Relevance
“…2020; 86(1): 83, 1-13. DOI: https://doi.org/10.5334/aogh.2885 confirmed the persistence of a low level of knowledge among the general public about stroke, and more specifically about risk factors and warning signs [10][11][12][13].…”
Section: Introductionmentioning
confidence: 77%
“…2020; 86(1): 83, 1-13. DOI: https://doi.org/10.5334/aogh.2885 confirmed the persistence of a low level of knowledge among the general public about stroke, and more specifically about risk factors and warning signs [10][11][12][13].…”
Section: Introductionmentioning
confidence: 77%
“…A domestic survey on the recognition of stroke among community residents in Chongqing found that the recognition rate of stroke warning symptoms was 30.7-75.6% [9]. A study of 1472 respondents found that sudden headaches (54.1%), vertigo (51.0%), and dyslexia (44.3%) were the most recognizable stroke warning symptoms [13].…”
Section: Discussionmentioning
confidence: 99%
“…Saudi Arabia suffers from a high prevalence rate of hypertension among the adult population, reaching 26.1% [ 20 ]. Additionally, the adult population showed a low awareness of hypertension as a risk factor for stroke [ 21 ] Our present study showed that one-third of the control group were hypertensive. Surprisingly, a study reported that only 23% of hypertensive patients in Saudi Arabia are aware of their blood pressure elevation [ 9 ].…”
Section: Discussionmentioning
confidence: 64%